MAKING APPLICATION HOMEPAGE GROUP BAND NOTHING ELSE USING MACROMEDIA FLASH MX - Kukuh Apit Haryanto; Ire Puspa W, Skom, MMSI Ire Puspa W, Skom, MMSI (Jurnal Sistem Informasi, 2007)
Internet increasingly being used by people around the world to obtain information.Because of extensive coverage, the internet is ideal for the medium used to spreadinformation globally. Homepage has a function as a source of information, services,music, entertainment, education, and others. The role of the homepage in theinformation age as it is now very helpful in disseminating information quickly.Therefore, in this scientific writing, the authors make a homepage which containsabout Nothing Else Group Band created using Macromedia Flash MX, which isexpected to help provide information more quickly to the music lovers in general andfans of Band Nothing Else Group which Fans called Nothing Else in particular.